The unmeasured labor force: The growth in work hours - Barry Bluestone; Stephen Rose (Levy Economics Institute of Bard College, 1998)
Is the current labor market as tight as official statistics would seem to indicate? If incumbent workers increase their hours of work, it is irrelevant to the unemployment rate, but hardly irrelevant to the level of labor supply. The authors of this brief find that job insecurity and stagnating wages have made Americans willing to work those extra hours to build a financial cushion, and a 1 percent increase in hours worked per worker for a fixed labor supply is equivalent in terms of labor supply to a 1 percent increase in the number of workers. This more realistic picture of labor supply has important implications for expectations that welfare recipients can easily find jobs, for reforms in labor market statistics to provide better information, and for the direction of monetary policy.
Keywords: 330